Plant ingredients in the formulation of meat products: review - Maksim Rebezov , Olga Neverova, Anton Nesterenko, Oksana Avtuyhova, Yuliya Zabalueva, Marina Prilepa (International Journal of Modern Agriculture, 2021)
The use of plant ingredients is widespread in the technology of production of meat products. Replacement of the main raw material (minced meat) with a plant component in the production process is primarily to reduce the cost of the product, and secondly, to give the meat product specific taste qualities and improve the functional and technological properties. In the article the methods of production of meat products (minced meat, sausages, pates, cutlets, etc.) with the addition of a plant ingredients are considered. Production of meat products with the use of ingredients of both animal and plant origin not only expands the range of products, but also promotes the rational use of raw material resources, providing the population with quality food products. Plant raw ingredients give new dietary properties to the product, increase biological value, improve organoleptic indicators of finished products, reduce its cost. Plant additives introduced into the formulation of meat products enrich with plant protein, dietary fiber, minerals, vitamins and other biologically active components.